Herbicides Persistence in Rice Paddy Water in Southern Brazil - Zanella, Renato; Adaime, Martha B.; Peixoto, Sandra C.; Friggi, Caroline do A.; Prestes, Osmar D.; Machado, Sérgio L.O.; Marchesan, Enio; Avila, Luis A.; Primel, Ednei G. (IntechOpen, 2011)
None